The push toward institutional control: Structural violence and youth in Hawaiʻi. Issue 2 (23rd April 2022) - King, Sanna
Abstract: Concerns surrounding juvenile delinquency point to neoliberal notions of youth responsibilization with no regard to the violence of structural oppressions and daily hardships, in which deviance could be a form of response. This article discusses the influence of and response to structural violence and oppression that resulted in daily hardships for youth, and for some youth, deviant behaviors that pushed them toward the criminal justice system. Drawing on in‐depth interviews with 64 participants and 532 pieces of youth writings in Hawaiʻi, this study examines how experiences with structural violence and oppression pushed youth in Hawaiʻi toward institutional control. Findings indicate the role racialized and gendered structures developed through colonialism had in the lives of youth in Hawaiʻi and their difficult experiences with family instability and patriarchal control that result in youth engaging in deviant coping mechanisms. Youth exhibited resilience in the face of hardship and methods of control that speak to the lack of choices youth have in places with histories of colonialism.